COMPLEX COMPOUND SENTENCES WITH SUBORDINATE CLAUSES EMPLOYED IN LITERARY STYLE - Bakirova Elnora Anvarovna (Modern American Journals, 2025)
The article examines complex subordinate compound sentences used in literary style, analyzing their types with illustrative examples. The multifaceted potential of literary speech is explored.
Keywords: Literary speech, figurative expressions in complex subordinate sentences, poetic style, prosaic style, syntactic function.